Eclectic Ocular Comorbidities and Systemic Diseases with Eye Involvement: A Review. (14th March 2016) - Pinazo-Durán, María D.; Zanón-Moreno, Vicente; García-Medina, José J.; Arévalo, J. Fernando; Gallego-Pinazo, Roberto; Nucci, Carlo
Abstract : Coexistence of several ocular diseases is more frequent than suspected. In spite of the refractive errors, one or more of the following can be detected simultaneously: glaucoma, cataracts, uveitis, age-related macular degeneration, and dry eyes. In addition, as people age, ocular comorbidities are much more usually seen. Specific diseases are openly acknowledged to affect the eyes and vision, such as diabetes mellitus, hypertension blood pressure, arthritis, hyperthyroidism, neurodegenerative disorders, hematologic malignancies, and/or systemic infections. Recent advances in early diagnosis and therapy of the ophthalmic pathologies have reinforced patient options to prevent visual impairment and blindness. Because of this, it is essential not to overlook sight-threatening conditions such as the ocular comorbidities and/or the eye involvement in the context of systemic disorders. Moreover, the important role of the multidisciplinary cooperation to improve and sustain management of patients affected with eclectic ocular comorbidities and/or systemic disorders with eye repercussion is specifically addressed. This review intends to shed light on these topics to help in making opportune diagnosis and appropriately managing the affected patients.